“Effect of Heat Treatment Variables on Microstructure and Mechanical Properties of Aisi 4130 Low Alloy Steel’’ (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The present study investigates the effect of heat treatment on the microstructure and mechanical properties of AISI 4130 steel. The material was subjected to a sequence of normalizing, hardening, and tempering treatments to evaluate the influence of tempering temperature on performance characteristics. Normalizing was carried out at 890°C followed by air cooling, resulting in a refined ferrite–pearlite microstructure. Subsequently, hardening was performed at 860°C and followed by quenching to obtain a martensitic structure.Tempering was conducted at two different temperatures, 472°C (Sample A) and 518°C (Sample B), to study the variation in mechanical behavior.The results highlight that tempering temperature plays a critical role in tailoring the balance between strength and toughness in AISI 4130 steel. This study provides useful insights for optimizing heat treatment parameters for engineering applications requiring a combination of mechanical performance and structural reliability.